Putting Inclusive Education into Practice: The Language of Universal Design for Learning (UDL) (Innovaciones Educativas, 2025)
Inclusive education (IE) is redefining educational systems around the world to prevent the exclusion ofstudents and centers the curriculum on the learner. It is grounded in the principles, guidelines, and checkpoints ofUniversal Design for Learning, known as UDL (Centre for Applied Special Technology [CAST], 2024). This descriptivestudy explored teachers’ knowledge and perceptions of inclusive education, specifically those who participated in the 16th Scientific Convention of Spanish Language Teachers: Language and Literature Without Barriers, heldfrom November 27 to 29, 2024. Participants engaged via the Padlet tool and responded to two questions: How caninclusive education be put into practice? What digital tools do you use most frequently for pedagogical mediation? The aim was to analyze the most common beliefs held by teachers when implementing inclusive education, identifypotential biases, and determine whether they associate these practices with Universal Design for Learning (UDL). The study concludes that teachers are familiar with inclusive education and have some understanding of UDL and its connection to inclusive practices. However, there is a clear need for further training and the integration of newtechnological tools to enhance pedagogical mediation.
Keywords: inclusive education; universal education; learning; education; access to education